Pengaruh Personal Attitude, Subjective Norm, dan Perceived Behavioral Control terhadap Entrepreneurial Intention - Alfian Loria; Rodhiah Rodhiah (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
This study aims to determine the effect of Personal attitude, subjective norm, dan perceived behavioral control toward entrepreneurial intention. This study uses a quantitative method in which data collected by researchers uses a survey method with the